2014
DOI: 10.1111/1744-7917.12168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of five antibiotics on larval gut bacterial diversity of Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: Larvae of the diamondback moth, Plutella xylostella L. (Lepidoptera: Plutellidae), have rich microbial communities inhabiting the gut, and these bacteria contribute to the fitness of the pest. In this study we evaluated the effects of five antibiotics (rifampicin, ampicillin, tetracycline, streptomycin sulfate and chloramphenicol) on the gut bacterial diversity of P. xylostella larvae. We screened five different concentrations for each antibiotic in a leaf disc assay, and found that rifampicin and streptomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 53 publications
3
54
3
1
Order By: Relevance
“…This lepidopteran is difficult to control because it has developed resistance to most classes of insecticides (Baxter et al, 2005; Zalucki et al, 2012). Many studies have focused on the bacterial diversity of the P. xylostella gut based on culturing and denaturing gradient gel electrophoresis (DGGE) methods (Indiragandhi et al, 2007; Lin et al, 2015a,b) but these only partially reveal the gut microbial diversity. Our previous study based on the sequencing of V6 region of 16S rRNA supplied a more complete understanding of the P. xylostella gut microbiota than earlier culturing-based studies (Xia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This lepidopteran is difficult to control because it has developed resistance to most classes of insecticides (Baxter et al, 2005; Zalucki et al, 2012). Many studies have focused on the bacterial diversity of the P. xylostella gut based on culturing and denaturing gradient gel electrophoresis (DGGE) methods (Indiragandhi et al, 2007; Lin et al, 2015a,b) but these only partially reveal the gut microbial diversity. Our previous study based on the sequencing of V6 region of 16S rRNA supplied a more complete understanding of the P. xylostella gut microbiota than earlier culturing-based studies (Xia et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In most of the cases, microbiota investigation highlighted interesting host-symbiont interactions, representing key aspects in insect's survival and adaptation, such as development, nutrition, detoxification, and maintaining of the immune system (Dillon & Dillon, 2004;Engel & Moran, 2013). Regarding lepidopterans, the studies on their bacterial communities have increased in the recent years, especially for insect pest moths such as Ostrinia nubilalis (Belda et al, 2011), Spodoptera littoralis (Tang et al, 2012), Lymantria dispar (Broderick et al, 2004;Lin et al, 2015), Helicoverpa armigera (Xiang et al, 2006), Plutella xylostella (Xia et al, 2013), and Bombyx mori (Liang et al, 2014). Furthermore, some of these studies revealed the role played by the bacteria in helping the host in a broad range of activities.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach that can be used to experimentally manipulate components of the bacterial microbiome is the use of (cocktails of) antibiotics that target specific bacterial groups, or temperature-shock treatments that affects some microbes more than others. With these approaches, the microbiome changes in composition, and the performance of insects can be compared with vs. without, or among different combinations of treatments (Bordenstein & Bordenstein, 2011;Lin et al, 2015). Although these methods provide an indication of potential links between microbiome and host, these are usually mere correlations and should therefore be interpreted with caution, as they might not infer causation.…”
Section: Approaches To Study Microbiome-host Interactionsmentioning
confidence: 99%